Remote patient monitoring in spine surgery - Farias, Frederico A. C.; Falavigna, Vincenzo F.; Viapiana, Maria Eduarda L.; Falavigna, Asdrubal (Journal of Musculoskeletal Surgery and Research)
Objectives: Remote monitoring or telemonitoring is an innovative strategy to improve patient care. This study aimed to present the authors’ experience of a remote monitoring platform for post-operative care of patients who have undergone spine surgery. Methods: A telemonitoring system for patients undergoing spine surgery, centered on a smartphone application named Wippe Track, (Brazilian Telemedicine Company BR HomMed, São Paulo, Brazil) compatible with both Android and iOS smartphones. All patients had two Bluetooth devices connected to the smartphone application: Digital scale and wristband activity tracker. The outcomes evaluated were based on patient-related outcome measures (PROMs) using specific disease-oriented questionnaires. Results: A preliminary study to refine the system based on patient/provider input was performed with 30 patients. The adherence and interaction with the platform were 94%. Patients have provided all the PROMs data inputs and have consistently interacted with monitoring center professionals and the surgeon through the platform. Weight loss was observed in 76% of overweight patients using remote nutritionist support and specific exercises. Conclusion: The patients were satisfied and felt secure. The remote monitoring could detect and help manage events and warnings related to post-operative issues and reduce the need to travel for non-scheduled care.